Prevalence and associations of anaemia among patients on chronic haemodialysis at a tertiary hospital in Limpopo Province - Muponda, Blessing Kudakwashe (My University, 2023)
Background: Anaemia is a very common cause of morbidity and mortality in patients with chronic kidney disease (CKD) on chronic haemodialysis7. The main aetiology of anaemia in CKD among patients on chronic haemodialysis is erythropoietin deficiency Aim: To determine the prevalence and associations of anaemia among patients on chronic haemodialysis at the PKDC in Limpopo Province, South Africa. Methods: A retrospective descriptive, cross-sectional quantitative study was performed at a single dialysis centre (PKDC) and included all patients on chronic haemodialysis over a one-year period (01/01/2019 to 31/12/2019). A standardized data collection form created on Epi Info Version 7 was used to collect data from 121 study participants’ hospital files. There was no sampling performed as all patients meeting the inclusion criteria were included in the study. The collected data was analysed using the SPSS Version 25. Results: A total of 121 patients were included in the study. In the final data analysis, 55.5%(n=66) were males and 45.4%(n=55) were females. The overall mean age was 41.9 ± 11.7 years. Using the WHO definition of anaemia (Hb< 13g/dl in males and Hb<12g/dl in females), prevalence of anaemia was 89.3% and 85% in male and female patients, respectively. All 121 (100%) patients were on erythropoietin (EPO). According to the 2012 KDIGO guidelines, the target Hemoglobin (Hb) in haemodialysis patients on EPO is between 10g/dl and 12g/dl. Using a Hb level < 10 g/dl to define anaemia, the overall prevalence of anaemia was 23.1%(n=28). The Chi-square test indicated that there were no associations between anaemia (Hb<10g/dl) and any of the clinical characteristics that were analyzed (all p-values > 0.05). Comparison of the means of two groups (Anaemia: No and Anaemia: Yes) using the t-test it was observed that the p-values were <0.001 and 0.007 for Hb and Albumin respectively. The null hypothesis was rejected, and we concluded that there was a difference between the Hb and albumin levels of patients who have anaemia (Anaemia Yes) and patients who do not have anaemia (Anaemia No), with a 5% significance level. There was no significant mean difference for the other laboratory variables. Conclusion: This study concludes that there was a low prevalence of anaemia (Hb<10g/dl) among the study population (23%) due to the high rates of EPO use (100%). There was no association between any of the clinical characteristics and anaemia. There was a difference between the Hb and albumin levels of patients who have anaemia (Anaemia Yes) and patients who do not have anaemia (Anaemia No), with a 5% significance level. There was no significant mean difference for the other laboratory variables.
Thesis (M.Med. (Internal Medicine)) -- University of Limpopo, 2023
Keywords: Anaemia; Haemodialysis; Chronic kidney disease; Haemoglobin; Anemia; Renal anemia; Chronic renal failure